Case Report: A long-term survival case of diffuse large B-cell lymphoma with left ventricular infiltration and spinal cord compression - Sun, Rui; Jin, Chenxing; Qin, Henan; Zhang, Wenhe; Ning, Zhen; Liu, Jiwei; Wang, Aman (Frontiers in Cardiovascular Medicine, 2023)
Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma and may occur with lymph node and/or extranodal involvement. However, DLBCL with intracardiac mass is exceedingly rare. In the reported literature, the intracardiac infiltration of DLBCL mostly involves the right ventricle. Lymphoma that invades the heart has an aggressive nature, with symptoms that are easily ignored initially and can lead to multiple complications in severe cases, resulting in a poor prognosis. Early screening and diagnosis may significantly improve the survival rate.Early diagnosis may significantly improve outcomes.